The relationship between perceived organizational support and sickness presenteeism among nurses in hospital inpatient wards - Dodi Wijaya; Indah Fatimatus Zahro; Yulia Kurniawati; Ahmad Rifai; Kholid Rosyidi Muhammad Nur (Nursing and Health Sciences Journal (NHSJ), 2025)
The phenomenon of increasing sickness presenteeism among healthcare workers, especially nurses, has raised serious concerns because it can potentially reduce the quality of healthcare services provided to patients. One of the factors contributing to the high level of sickness presenteeism among nurses is the perceived organizational support they feel. This study aimed to examine the relationship between perceived organizational support and sickness presenteeism of nurses in hospital inpatient wards. This research used a quantitative correlational method with a cross-sectional approach. The sampling technique employed was purposive sampling, involving 91 nurses assigned to the inpatient wards of Jember Klinik Hospital and Kaliwates Hospital in Jember. The research instruments included the Stanford Presenteeism Scale (SPS-6) and the Perceived Organizational Support Scale, both of which have been validated for their reliability. Data analysis was conducted with Kendall's Tau-B test. The results showed a very significant relationship between perceived organizational support and sickness presenteeism among nurses in the inpatient wards. The statistical analysis results show a significance value (p-value) of 0.001, indicating a significant relationship, and a correlation coefficient (r = 0.939), indicating a robust positive correlation. In this study, higher POS scores represented higher perceived support, while higher SP scores represented greater sickness presenteeism, thus explaining the positive correlation. The findings indicate that low perceived organizational support is significantly associated with higher levels of sickness presenteeism among nurses. This study concludes that low perceived support from head nurses influences the high level of sickness presenteeism in nurses.